(untitled) (Revista Apotheke, 2021)
This article presents a proposal for a Laboratory-School by John Dewey, which highlights the presence of a space dedicated to a museum within the school environment. To analyze this proposal, it was necessary analyze the educational function of the museum and its educational causes both at school and outside it.